Tumor Suppressor LINC02487 Inhibits Oral Squamous Cell Carcinoma Cell Migration and Invasion Through the USP17–SNAI1 Axis - Feng, Lu; Zhang, Jianjun; Sun, Minglei; Qiu, Feng; Chen, Wantao; Qiu, Weiliu (Frontiers in Oncology, 2020)
Purpose: The aim of this study was to explore the functions and associated mechanisms of long noncoding RNA LINC02487 in oral squamous cell carcinoma (OSCC). Methods: The relative expression levels of LINC02487 in OSCC cell lines and tissue samples were examined by RT-qPCR. Intracellular localization was determined using RNA fluorescence in situ hybridization. LINC02487 was cloned into the pCMV-puro vector and then introduced into OSCC cells using lentiviral transfection. Cell processes such as proliferation, apoptosis, migration, and invasion were subsequently examined. LINC02487-binding proteins were identified by ChIRP–MS and confirmed by RNA immunoprecipitation. Protein expression was determined by western blotting assay. Results: LINC02487 has been reported to be downregulated in OSCC. Here, we confirmed that the expression of LINC02487 was reduced in 6 OSCC cell lines compared with that in immortalized normal oral epithelial cells, and in 50 OSCC samples compared with paired adjacent normal tissue in a Chinese population, and that LINC02487 expression levels were associated with cancer metastasis. We further identified that LINC02487 was localized to the cytoplasm, aggregated around the nuclear membrane. Functional studies demonstrated that overexpression of LINC02487 significantly suppressed cell migration and invasion, and also inhibited cell proliferation. For the mechanism, we revealed that LINC02487 directly binds to USP17, a deubiquitinating enzyme, and regulates cell migration and invasion through the USP17–SNAI1 axis in a process that involves epithelial–mesenchymal transition (EMT). Conclusion: Our results confirmed that long noncoding RNA LINC02487 is downregulated in OSCC tissue samples and cell lines. We also found that LINC02487 acts as a tumor suppressor through the USP17–SNAI1 axis.